Experımental Investıgatıon Of The Effects Of Dıfferent Dırect Bondıng Materıal - Sadık Meral; Yalçın Işımer; Deniz Sağdıç (Galenos Yayinevi, 1990)
In this study, the adherence capacity of three bonding adhesive resins of the human teeth enamel have beencompared in vitro. This comparison was performed by stricking the metal brackets of shear strengths and tensile was found at the highest level. In other bonding adhesives of bracket was turned out on the 80 % infereface of adhesive/enamel.